The literary workshop as a pedagogical strategy in the classroom - Peraza Rodríguez, Mario (Rastros Rostros, 2020)
The subject of this article addresses the literary workshop as a didactic device in the teaching of literaturesupported by sufficient theoretical and methodological supports that clearly support its development in theclassroom. Since the development of the research project of Master in Pedagogy of the District University,whose name is “Creation from the autobiographical chronicle: a strategy for the development of literaryeducation.” Findings are found in which they demonstrate certain ambiguities regarding the skills that theliterary workshop strengthens, as well as the almost exclusive focus on reading, suppressing to some extentthe creative writing processes in relation to an implicit methodological framework that due to its Informalitycannot contribute to the development of the workshop as an organized pedagogical device. There are multiplevoices that have spoken about the literary workshop: some from their experience in the development of thesespaces for literary creation; others from the literary reading workshop in formal school settings; many others,from a point of view of the training of writers and the problem of the teachability of literature as a professionaltraining career. Gianni Rodari (1973), Louise Rosenblatt (1978), Benigno Delmiro Coto (2001), and finally, TeresaColomer (2001). Likewise, other proposals such as the creative writing workshops by RELATA (Ministerio deCultura, 2010), show ways of systematizing literary artistic practice. This work dialogues from perspectivesgenerating strategies that unite the literary creation workshop and the pedagogical workshop in the context ofthe Pedagogy of Literature.
Keywords: : Educational workshop; creative writing; Reading